Histamine H2 receptor desensitization: involvement of a select array of G protein-coupled receptor kinases - Shayo, Carina Claudia (2001)
The histamine H2 receptor (H2r) belongs to the heptahelical receptor family; upon agonist binding, members of this family activate a G protein and the downstream effector adenylyl cyclase. Like other G protein-coupled receptors, exposure of H2r to agonists produces a desensitization of the response. The present study focused on the desensitization mechanism of this receptor. Using transiently transfected COS-7 cells expressing tagged-H2r, the desensitization induced by amthamine, characterized by decreased cAMP production, was studied. Results show that the receptor was rapidly desensitized with a t1/2 0.49 0.01 min. Because of the rapid nature of H2r desensitization, receptor phosphorylation was examined as a likely mechanism for signal attenuation. H2r desensitization was not affected by protein kinases A and C (PKA and PKC) inhibitors but was remarkably reduced by Zn2, an inhibitor of G protein-coupled receptor kinases (GRKs). Cotransfection experiments using tagged H2r and different GRKs (2, 3, 5, or 6), demonstrated that GRK2 and GRK3 were the most potent in augmenting desensitization, causing a reduction in the maximal response to   amthamine and a decrease of the t1/2 for desensitization, whereas GRK5 and GRK6 did not affect the signaling. Receptor phosphorylation correlates with desensitization for each GRK studied, whereas phosphorylation that is dependent on protein kinases A and C seemed irrelevant in receptor signal termination. These results indicate that in H2rtransfected COS-7 cells, exposure to an agonist caused desensitization controlled by H2r phosphorylation via GRK2 and GRK3.